Synthesis of bismuth oxide nanoparticles at 100 degrees C - Patil, M. M.; Deshpande, V. V.; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of ultrafine Bi2O3 particles at 80-100 degrees C under refluxing conditions. Freshly prepared bismuth hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 6-12 h. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. The thermal decomposition of bismuth hydroxide yields Bi2O3 only at 400 degrees C. This shows the advantage of the present method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these oven-dried powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction